A model of Charles Ponzi - Gadi Barlevy; Inês Xavier (Federal Reserve Bank of Chicago, 2025)
We develop a model of Ponzi schemes with asymmetric information to study Ponzi frauds. A long-lived agent offers to save on behalf of short-lived agents at a higher rate than they can earn themselves. The long-lived agent may genuinely have a superior savings technology, but may be an imposter trying to steal from short-lived agents. The model identifies when a Ponzi fraud can occur and what interventions can prevent it. A key feature of Ponzi frauds is that the long-lived agent builds trust over time and improves their reputation by keeping the scheme going.
Keywords: C73; D82; G51; K42; L14; 330; Ponzi scheme; asymmetric information; reputation; fraud